Assessment of kernelrazzo exposed to aggressive environments. (30th December 2015) - Olusola, Kolapo Olubunmi; Babafemi, Adewumi John
Highlights: Durability assessment of kernelrazzo in aggressive environment was carried out. Performance of kernelrazzo was evaluated in acid, sulphate and alkaline media. Effect of replacing MC with PKS and GD on deterioration factors were evaluated. Acid environment had the most severe effect on kernelrazzo . 25% PKS and 30% GD contents are recommended for optimum performance of kernelrazzo . Abstract: The performance of kernelrazzo, a variant of terrazzo, has been investigated under chemically aggressive environments with a view to establishing its suitability for use as an alternative to terrazzo floor finish. Results revealed that the higher the concentration of the aggressive media, the higher its impact on the mass loss and compressive strength of specimens. On a comparative basis, acid environment had the greatest compressive strength deterioration factor after 56 days. Specimens subjected to alkaline environment show partial disintegration at 50% palm kernel shell content. However, in all the aggressive environments, optimum replacement level of marble chipping was obtained with 25% palm kernel shell and 30% granite dust contents.